BACK COVER - Wiguna, Putu Perdana Kusuma (International Journal of Biosciences and Biotechnology; Vol 8 No 2 (2021): International Journal of Bioscience and Biotechnology, 2021)
BACK COVER IJBB VOL. 8 NO. 2 APRIL 2021